2019
DOI: 10.1242/jeb.207985
|View full text |Cite
|
Sign up to set email alerts
|

C-type allatostatin and its putative receptor from the mud crab serve an inhibitory role in ovarian development

Abstract: C-type allatostatins are a family of peptides that characterized by a conserved unblocked-PISCF in C-terminal. In insects, it is well known that C-type allatostatin has a potent inhibitory effect on juvenile hormone biosynthesis by the corpora allata. Recently, C-type allatostatin has been widely identified from crustacean species but little is known about its roles. Therefore, this study described the tissue distribution patterns of C-type allatostatin and its putative receptor in the mud crab Scylla paramamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Recent studies have found that several peptide hormones are also involved in crustacean reproduction. This includes the pigment-dispersing hormone (PDH) (6), neuroparsin (7), red pigment concentrating hormone (RPCH) (8), neuropeptide F (NPF) (9), short neuropeptide F (sNPF) (10), and allatostatin (AST) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that several peptide hormones are also involved in crustacean reproduction. This includes the pigment-dispersing hormone (PDH) (6), neuroparsin (7), red pigment concentrating hormone (RPCH) (8), neuropeptide F (NPF) (9), short neuropeptide F (sNPF) (10), and allatostatin (AST) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crustacean female sex hormone (CFSH), isolated from the sinus gland of the blue crab Callinectes sapidus, is considered to be the female sex-determining hormone [29]. Besides in S. paramamosain, the red-pigment concentrating hormone (RPCH), secreted from the eyestalk ganglion, stimulates ovarian development, while the short neuropeptide F (sNPF) and allatostatin-C show inhibitory effect on ovarian development [30,31]. In P. pelagicus, it was reported that the PpOT/VP-like peptide could inhibit the release of steroid hormones (17β-estradiol and progesterone) in ovarian explants in vitro [19].…”
mentioning
confidence: 99%
“…argus , its expression in LF is low compared to the brain. Liu et al [ 110 ] reported that AstC neuropeptide is expressed in the olfactory lobe of decapod crustaceans. The function of the AstC signaling in decapod OSNs and olfactory lobes is unclear, but AstC has been shown to modulate olfactory learning and pheromone sensitivity in insects [ 111 ], and influences circadian rhythm and immunity [ 112 , 113 ].…”
Section: Discussionmentioning
confidence: 99%